Early evidence of irrigation technology in the North China Plain: Geoarchaeological investigations at the Anshang Site, Neihuang County, Henan Province, China. Issue 2 (13th July 2017) - Storozum, Michael; Liu, Haiwang; Qin, Zhen; Ming, Kongde; Fu, Kui; Wang, Hui; Kidder, Tristram
ABSTRACT: The development of irrigation is a politically important technology that enabled agricultural societies to intensify agricultural production. In the North China Plain, the historical record suggests a long tradition of irrigation, but archaeologists have found scant evidence of these technologies outside of urban areas. In 2012, 2015, and 2016, our excavations at the Anshang site, Neihuang County, Henan Province, China, revealed several archaeological features that we interpret as evidence of Late Shang dynasty ( ca . 1200–1046 B.C.) canal construction in a nonurban context. By using a range of geological methods, including particle size, loss on ignition, magnetic susceptibility, and micromorphology, we suggest that these ancient canals and the subsequent construction phases found at Anshang not only influenced the development of local geomorphic conditions, but also were part of early dynastic attempts to restructure the natural landscape to facilitate agricultural productivity. These irrigation canals found at Anshang may be representative of broader trends of human‐environmental interactions in the North China Plain.